Gli inizi di AVSI a Belo Horizonte - DOI: 10.5752/P.2316-1752.2009v16n18/19p17 - Alberti, Arturo (Cadernos de Arquitetura e Urbanismo, 2010)
This paper is a record of the presence of AVSI in Brazil. It explains the methodological approach to the problem of slums in the cities of Belo Horizonte, Minas Gerais State, and Salvador, Bahia State. The success of the interventions, which have transformed slum dwellers into citizens with rights and duties, is due to three factors: support to a real presence; wide popular participation; and acquisition of the deed of property of the lot. Key words: Slums; Property legalization; Subsidiarity.